Engineering chemically exfoliated dispersions of two-dimensional graphite and molybdenum disulphide for ink-jet printing. (2nd November 2016) - Michel, Monica; Desai, Jay A; Biswas, Chandan; Kaul, Anupama B
Abstract: Stable ink dispersions of two-dimensional-layered-materials (2DLMs) MoS2 and graphite are successfully obtained in organic solvents exhibiting a wide range of polarities and surface energies. The role of sonication time, ink viscosity and surface tension is explored in the context of dispersion stability using these solvents, which include N-methyl-2-pyrrolidone (NMP), N, N -Dimethylacetamide (DMA), dimethylformamide (DMF), Cyclohexanone (C), as well as less-toxic and more environmentally friendly Isopropanol (IPA) and Terpineol (T). The ink viscosity is engineered through the addition of Ethyl-Cellulose (EC) which has been shown to optimize the jettability of the dispersions. In contrast to prior work, the addition of EC after sonication—instead of prior to it—is noted to be effective in generating a high-density dispersion, yielding a uniform film morphology. High-quality inks are obtained using C/T and NMP as solvents for MoS2 and graphite, respectively, as gauged through optical absorption spectroscopy. Electronic transport data on the solution-cast inks is gathered at room temperature. Arrays of 2D graphite-rod based inks are printed on rigid Si, as well as flexible and transparent polyethylene terephthalate (PET) substrates. The results clearly show the promise of ink-jet printing for casting 2DLMs into hierarchically assembled structures over a range of substrates for flexible and printed-electronics applications.